Deformation and energy distribution of metal tubes under internal explosive loading. (September 2019) - Feng, L N; Li, D; Tian, J D; Zhang, Z F; Hu, Z X
Abstract: Deformation and energy distribution of two kinds of metal tubes under internal explosive loading have been studied by means of experiments and simulations in this paper. The velocity and displacement-time history of characteristic points on the flat metal tubes were measured by Photonic Doppler Velocimetry (PDV). Ls-dyna fluid-solid coupling algorithm was used to simulate the experiment. Simulation results agree well with the experimental results. On this basis, the expansive properties of the round tube in the same condition were obtained, the round tube directly expands to the maximum diameter, does not like the expansion and contraction fluctuant process of the flat tube. The simulation result shows that the flat tube will output more energy in the form of kinetic energy, while the round tube tends to store energy in the form of plastic strain energy.